Application of international financial reporting standards for small and medium-sized entities in European countries - Dragičević, Predrag (Economic Outlook, 2023)
The work is aimed at researching the International Financial Reporting Standard (IFRS) for small and medium-sized entities (MSE) in European countries and the frequency of adoption and application of this standard. The first part of the paper emphasizes the importance of this standard, its benefits and some of the obstacles to its application, which are recognized as significant in the previous literature. All references in the previous literature reviewed for the purposes of this work are followed up by the research that was conducted. The research aims to determine how often IFRS is applied to SMEs in European countries. The data was collected from reports published by the IFRS Foundation, which contain data on the application of the standard adapted for MSEs. The data were processed with descriptive statistics. The research showed that a small number of European countries apply IFRS for MSEs, and that European countries that are in the EU are not more inclined to apply IFRS for MSEs.